Vascular Pseudoinvasion: A Case Report and Review of Literature. (11th September 2019) - Agarwal, Anupma; Wu, Hueizhi
Abstract: In the era of minimally invasive procedures, laparoscopic hysterectomy is preferred over total abdominal hysterectomy as the primary treatment of endometrioid cancer limited to the uterus. Lymphovascular invasion (LVSI) is an important prognostic indicator for this tumor. Studies have observed presence of vascular pseudoinvasion in the surgical specimen excised via laparoscopic hysterectomy. Some studies have reported no increase in LVSI after minimally invasive surgery, implying that there is no vascular pseudoinvasion. Here, we present a 59-year-old female with history of obesity, hypertension, diabetes mellitus, asthma, and biopsy-proven well-differentiated endometrioid adenocarcinoma who underwent total laparoscopic hysterectomy with bilateral salpingo-oophorectomy and sentinel node dissection. An ill-defined friable mass (2.1 cm in maximum dimension) was present in the posterior lower uterine segment and had the morphology of endometrioid adenocarcinoma, grade 1 out of 3, invasive into the outer half of myometrium. There was no true vessel invasion but rather abundant contamination—smearing of tumor into vascular spaces. An immunostain for D2-40 identified no lymphatic invasion. Immunostains for CD31 and CD34 highlighted tumor cells present in vascular spaces consistent with pseudoinvasion. No regional lymph node metastasis was seen. Peritoneal fluid did not show malignant cells. After surgery, the patient received radiotherapy and had no evidence of recurrent disease. It has been proposed that the artifact of vascular invasion as seen in our case could be associated with the technique of laparoscopic hysterectomy. Substantial LVSI, in contrast to focal or no LVSI, has been shown to be the strongest independent prognostic factor for pelvic regional recurrence, distant metastasis, and overall survival. Its presence is a deciding factor for the type of adjuvant therapy. Therefore, it is important to recognize vascular pseudoinvasion to avoid misdiagnosis of LVSI.